Is GRDP a mediating factor in enhancing local tax revenues due to ICT development in Indonesia? - Priambodo, Aji; Anwar, Nurul; Suharno (Nurture, 2024)
Purpose: This study aims to investigate whether the Gross Regional Domestic Product (GRDP) of the information and communication sector mediates the relationship between Information and Communication Technology (ICT) development and local tax revenue enhancement across districts and municipalities in Indonesia. Design/Methodology/Approach: This study uses a quantitative approach to examine how ICT growth, access, infrastructure and utilization affect local taxes and regional levies using panel data from 2017 to 2021.The GRDP of the information and communication sector is incorporated as a crucial moderating variable. Findings: The findings reveal that the GRDP of the information and communication sector plays a vital moderating role in the relationships between ICT factors and local taxes and levies. ICT development benefits local tax systems through increased efficiency, transparency, reduced disparities and enhanced accessibility. Effective ICT infrastructure enables digital fiscal transactions, increasing revenues while improving collection efficiency and reducing income disparities among provinces. High ICT utilization supported by technological proficiency enables local governments to enhance local taxes and levies. Practical Implications: An increase in the GRDP of the information and communication sector leads to higher tax revenues for local governments, funding public services and infrastructure development. Additionally, it attracts investments from other sectors, boosting regional levies and promoting overall regional economic development. The study highlights leveraging the GRDP of this sector as a strategic factor to enhance local tax revenue and regional levies across Indonesian provinces contributing to fiscal decentralization efforts.